Linking Tax Morale and Personal Income Tax in Spain - Pilar Rey-del-Castillo; Jaime Villanueva-Garcia (Center for Economic Studies and ifo Institute (CESifo), 2018)
The paper presents a study of the relationship between the tax morale and the individual payments of personal income tax using the statistical matching of opinion polls with a representative sample of the personal income tax returns in Spain. As an initial step, the method selected to execute the match -imputations using Bayesian Networks- is described. The relationship between a proxy variable of the individual tax morale and other variables in the declared income tax file is later analyzed using the matched files. A first result is that tax morale increases with the level of declared wages, salaries and capital gains, while it has no link with declared business income.
Keywords: C10; C65; H24; H26; 330; statistical matching; opinion polls; personal income tax; tax morale